The Berenstain Bear Scouts and the run-amuck robot - Berenstain, Stan; Berenstain, Jan; Berenstain, Michael (New York : Scholastic, 1997)
When Professor Actual Factual's latest invention, the electronically supercharged robot named Robow, runs wild, it's time for the Berenstain Bear Scouts to take control.